2021
DOI: 10.3389/fphar.2021.715577
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Clinically Relevant Drug–Drug Interaction Between Rosuvastatin and Clopidogrel and the Risk of Hepatotoxicity

Abstract: Purpose: The combination therapy of rosuvastatin (RSV) and the platelet inhibitor clopidogrel (CP) is widely accepted in the management of cardiovascular diseases. The objective of the present study was to identify the mechanism of RSV–CP DDI and evaluate the risk of hepatotoxicity associated with the concomitant use of CP.Methods: We first studied the effect of CP and its major circulating metabolite, carboxylic acid metabolite (CPC), on RSV transport by overexpressing cells and membrane vesicles. Second, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Meanwhile, abnormal liver function could be found in chronic heart failure ( Tavazzi et al, 2008 ). Inhibition of intestinal breast cancer resistance protein (BCRP) transporters by clopidogrel is likely to be a contributor of hepatotoxicity ( Ning et al, 2021 ). Once daily clopidogrel is advised to be taken either in the morning or evening, while rosuvastatin in the evening.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, abnormal liver function could be found in chronic heart failure ( Tavazzi et al, 2008 ). Inhibition of intestinal breast cancer resistance protein (BCRP) transporters by clopidogrel is likely to be a contributor of hepatotoxicity ( Ning et al, 2021 ). Once daily clopidogrel is advised to be taken either in the morning or evening, while rosuvastatin in the evening.…”
Section: Discussionmentioning
confidence: 99%
“…As of now, there is inadequate research to suggest that the combination of antibiotics and chemicals may result in potential drug–drug interactions and influence the development of drug-induced liver injury. 90 , 91 Yoo et al 92 proposed that when patients taking lovastatin undergo antibiotic therapy, there may be undesirable pharmacokinetic effects owing to the inhibition of gut microbiota. Inadequate control of plasma cholesterol levels has implications for the development of hepatic steatosis.…”
Section: Common Liver Injury–causing Drugs Linked To Gut Microbiotamentioning
confidence: 99%
“…To date, there are not enough studies showing that the combination of antibiotics and chemical agents might lead to potential DDIs and impact the development of DILI (100,101). Yoo et al (102) indicated that antibiotic treatment of patients taking lovastatin might lead to adverse pharmacokinetic effects by suppressing GM.…”
Section: Antibiotics Combined With Chemical Agentsmentioning
confidence: 99%